2023
DOI: 10.3390/biomedicines11020575
|View full text |Cite
|
Sign up to set email alerts
|

Spacer-Supported Thermal Ablation to Prevent Carbonisation and Improve Ablation Size: A Proof of Concept Study

Abstract: Thermal ablation offers a minimally invasive alternative in the treatment of hepatic tumours. Several types of ablation are utilised with different methods and indications. However, to this day, ablation size remains limited due to the formation of a central non-conductive boundary layer. In thermal ablation, this boundary layer is formed by carbonisation. Our goal was to prevent or delay carbonisation, and subsequently increase ablation size. We used bovine liver to compare ablation diameter and volume, creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The relation between carbonisation and ablation size has been extensively discussed in an author's previous study [29]. It can be concluded that minimising the chance of carbonisation leads to an increase in ablation rate, which is beneficial in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relation between carbonisation and ablation size has been extensively discussed in an author's previous study [29]. It can be concluded that minimising the chance of carbonisation leads to an increase in ablation rate, which is beneficial in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Postprocedural MR-based monitoring with its clear imaging, thermometric capabilities and sequence-based motion correction [34,35], along with CT and ultrasound, is one of the most effective tools for assessing ablation success within the first 24 h after ablation procedures [36]. As discussed in a preceding study, the comparison of manual volumetry through displacement of water and MR-based volumetry shows no statistically significant difference [29]. As such, MRbased volumetry is well suited as a non-invasive measuring method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation